The Influence Of Incentives On Employee Achievement: Case Study at PT. NCS Line World Wide - Cholifah, Siti; Lestari, Endang Dwi (Jurnal Ilmiah Manajemen Kesatuan, 2023)
Providing incentives is very important to pay attention to, because this is related to the work results of employees in carrying out their work. The purpose of this research is to determine the incentives given to employees, employee work performance at PT. Ncs Line World Wide in question, as well as the magnitude of the influence of incentives on increasing the work performance of PT employees. Ncs Line World Wide. The hypothesis of this research is that incentives have a significant effect on employee work performance at PT Ncs Line World Wide . The population is employees of PT. Ncs Line World Wide Jakarta numbered 157 people while the sample numbered 61 people. Samples were taken using the Slovin method, while the data analysis method used was the interview and questionnaire method with the results of a simple linear regression equation test with the help of SPSS program tools. Based on the research results, it shows that the incentive variable influences the work performance of PT employees. Ncs Line World Wide based on a calculated value (R) of 0.716 and a coefficient of determination (R2) of 0.569, this shows that incentives have an influence of 56.90% on employee work performance at PT. Ncs Line World Wide